KNOWLEDGE AND AWARENESS RELATED TO DIABETES MELLITUS AMONG UNIVERSITY STUDENTS IN SOUTH AFRICA: A CROSS-SECTIONAL STUDY. - Sanelisiwe Sibusisiwe Vaminhlanhla Ndlovu; Ziningi Nobuhle Jaya; Nokukhanya Thembane (Student's Journal of Health Research Africa)
Introduction